Use of the Automated Design-Time Environments for Research of Dynamics of Mechanical Systems - Valeriy Ponyatsky; Alexey Romanov (Современные информационные технологии и IT-образование, 2020)
In developing the complex optical techniques, the choice of a stepped motor is an arduous task. A methodology for estimating the power of the stepped motor has been developed, based on the use of CAD SOLIDWORKS and Matlab/Simulink. A dynamic model has been developed for a pancratic lens mechanism, which makes it possible to determine the required torque developed by the engine, taking into account the effect of springs, a complex profile and programmed change in the angle of rotation of the cam gear. This technique includes several stages. The essence of the first stage is to transform a 3D CAD SolidWorks model into a model in the MatLab environment. First, the 3D model is exported to an xml data file using the Simscape Multibody Link translator. After exporting to an xml file, the model is imported directly into the Simscape Multibody Model. When translating Simulink bodies receive the corresponding mass-inertial characteristics of SolidWorks assembly components, as well as mates between the bodies of the SolidWorks 3D model, which are converted to the degrees of freedom of dynamic Simulink bodies. In fact, when translating a dynamic model of the mechanism is constructed. To provide visualization of the Simulink model, the geometry of the SolidWorks assembly elements is transferred using translated stl files. The second step was to refine the resulting dynamic model.